ESTIMATE OF THE METALLIC CONTAMINATION OF THE URBAN EFFLUENTS BY THE EFFLUENTS OF THE MOHAMED V HOSPITAL OF MEKNES - Nour-eddine, Ameziane; Lahcen, Benaabidate (European Scientific Journal, ESJ, 2014)
The Mohamed V hospital of Meknes is one of the most important establishments for public health in the entire region of Meknes-Tafilalet; it is also one of the biggest sanitary structures of Morocco. According to the classification of the American Hospital Association (American Hospital Association [AHA], 1986) based on the number of active beds, this hospital belongs to class 7, with a real bed capacity of 531 beds among which 416 are functional, hence this has led to the importance of the study of the impacts of its effluents on the environment. Wastewaters of this hospital contain pollutions of microbiological, chemical, organic, mineral and metallic nature. They are rejected in the sewer system of the city without any preliminary treatment and has a loosened open-air at the level of Aïn Choubbik district where they are reused by the local residents for the irrigation of truck farm, cereal and tree-dwelling farm. Moreover, the major part of these wastewaters is poured into Bourouh river, in particular during pluvial period. Consequently, we may note direct harmful impacts on the health of Man as well as on the environment with its diverse compartments, water (Surface Water and subsoil water), ground and air. Thus, we will try using this present study to evaluate the pollution rate by elements in state of trace, taking a case of heavy metals effluents of the Mohamed V hospital of Meknes and the consequences it could have on the environment and as well as the proposed solutions. So, we are also going to estimate the pollution rate by these elements at the levels of urban wastewaters of the Ain Choubbik district receptacles of the hospital effluents.